Beyond Balanced Growth - Rebelo, Sergio; Kongsamut, Piyabha; Xie, Danyang (Washington, D.C. : International Monetary Fund, 2001)
Balanced growth models are commonly used in macroeconomics because they are consistent with the well-known Kaldor facts regarding economic growth. These models, however, are inconsistent with one of the most striking regularities of the growth process-the massive reallocation of labor from agriculture into manufacturing and services. This paper presents a simple model consistent with both the Kaldor facts and the dynamics of sectoral labor reallocation. The model shows that balanced growth can be consistent with structural change.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet